Anti-cancer activity of hierarchical ZSM-5 zeolites synthesized from rice-based waste materials. Issue 1 (20th December 2017) - Jesudoss, S. K.; Vijaya, J. Judith; Kaviyarasu, K.; Kennedy, L. John; Jothi Ramalingam, R.; Al-Lohedan, Hamad A.
Abstract : We report the organic template-free synthesis of hierarchical ZSM-5 zeolite using waste materials, by a simple hydrothermal method and their excellent anti-cancer activity against A549 human lung epithelial cell lines. Abstract : Herein, organic template-free MFI-type ZSM-5 zeolites were successfully synthesized by the hydrothermal method using waste materials such as rice husk ash (RHA), rice hull ash (RHuA), and rice straw ash (RSA). The waste materials were locally obtained, precleaned, and properly heat-treated to produce a high-purity crystalline SiO2 that was used in the synthesis of ZSM-5 zeolites under autogenous pressure in a short reaction time (5 days). The mineralogical phases, morphology, textural and thermal properties of the synthesized products were investigated by X-ray diffraction (XRD), Fourier transform infrared (FT-IR), Raman spectroscopy, high-resolution scanning electron microscopy (HR-SEM), N2 adsorption/desorption isotherms (BET), temperature-programmed desorption (NH3 -TPD), and thermogravimetric analysis (TGA/DTA). The as-synthesized ZSM-5 zeolites showed good crystallinity, and no amorphous material existed in the framework of the ZSM-5 zeolites after calcination and ammonium exchange processes. The characterization results prove that the high crystallinity of RHA as compared to that of the other materials (RHuA and RSA) is due to the high silica content in RHA. The transformation occurs from high-crystallinity RHA into ZSM-5 zeolite and also increases the crystallinity of zeolites. In addition, we have investigated hierarchical ZSM-5 zeolites at various concentrations for their potential cytotoxicity effect against the human lung epithelial cancer A549 cells.